TINJAUAN BAURAN PEMASARAN DI CITY EDGE CAFE JATINANGOR - Sugiarto, Yayan; Alfan Gymnastiar, Muhammad (JURNAL PARIWISATA VOKASI, 2024)
This study aims to analyze the effectiveness of the marketing mix at City Edge Café Jatinangor, focusing on four main elements product, price, place, and promotion. Using a Likert scale, this research evaluates customer perceptions of the performance of each aspect of the marketing mix and identifies areas requiring improvement. The research method used is descriptive, with data collection techniques including the distribution of questionnaires and observation. The results show that the product aspect is rated "Adequate" (54%), with potential for improvement in innovation and menu variety. The price aspect is also rated "Adequate" (42%), with challenges related to price transparency, discounts, and affordability that need to be addressed. The assessment of the place aspect reveals less satisfactory results, with ratings of "Adequate" (32%) and "Poor" (39%), indicating a need for improvements in location selection, accessibility, facilities, and visibility. The promotion aspect received a "Poor" rating, with dominant categories of "Adequate" (46%) and "Poor" (31%), highlighting deficiencies in the effectiveness of promotional messages, strategy innovation, and promotional frequency